Stay sane in an insane world : how to control the controllables and thrive - Harden, Greg; Hamilton, Steve, 1961- (Blackstone Publishing, 2023)
Greg Harden changes lives. This is why hundreds of world-class athletes, doctors, lawyers, teachers, business leaders, college students, and professionals from all walks of life have come to him for advice and direction--including 7-time Super Bowl Champion Tom Brady, 23-time Olympic Gold Medalist Michael Phelps, Heisman Trophy winners Desmond Howard and Charles Woodson, CEOs of major companies, and championship coaching staffs from all over the world. Harden teaches his students how to practice, train, and rehearse to give 100 percent, 100 percent of the time, and challenges them by asking: If you don't believe in yourself, why should I believe in you? Champions aren't born. They're built. Greg Harden spent over 30 years building them at the University of Michigan, including 400 future professional athletes, 50 NFL first-round draft picks, and 120 Olympians from over 20 countries. He gained national recognition when 60 Minutes Sports profiled him as "Michigan's Secret Weapon." Now, in his first book, Greg Harden is reaching out to help anyone who wants to live their best life by offering powerful and practical advice.